URANIUM-LEAD ISOTOPE AGE OF THE VEPSIAN OF KARELIA - Bibikova Y.V.; Kirnozova T.I.; Lazarev Y.I.; Makarov V.A.; Nikolayev A.A. (My University, 1990)
The U-Pb isotope dating of zircons of the second variety was done by the accepted laboratory procedure. Uranium and lead concentrations were determined by the isotopic dilution method. The lead-isotope composition was measured with the Cameca TSN-206A mas spectrometer by the thermionic emission method, using silica gel as the ion emitter. The zircons have the relatively high uranium content and high Tb/U ratio characteristic of minerals of alkalic rocks and associated pegmatites. The maximum 207Pb/ 206Pb age of zircons, 1756 m.y., can be regarded, as the minimum age of their formation. On the concordia diagram, the points for the zircons define a discordia whose upper concordia intercept corresponds to a value of 1765 ± 40 m.y. The error of the age calculated from the upper concordia intercept is significantly reduced giving zircon 1770 ± 12 formation Their age reliably fixes the upper boundary of the Vepsian in the chronostratigraphic scheme devised for the Lower Proterozoic of the Baltic shield and allows the Vepsian dolorite and the rapakivi-granite complexes to be firmly correlated with different stages of endogene activity.
Keywords: Proterozoic; Precambrian::Proterozoic; Докембрий::Протерозой